Denying to Embracing: A Mother’s Path to Acceptance, Love, and Resilience in Raising a Child with Down Syndrome - Alyanna V. Zabala; Araceli C. Doromal (Philippine Social Science Journal, 2025)
Grounded in phenomenology, this qualitative study explores the lived experiences of five mothers in the Negros Island Region raising children with Down Syndrome. The findings reveal a transformative journey from initial denial to profound acceptance, characterized by resilience in the face of challenges such as caregiving exhaustion and worries about the future. Anchored by faith and a focus on life skills, these mothers shifted their expectations to embrace unconditional love and their children’s potential for independence. These insights underscore the need for enhanced public awareness and community support systems, while suggesting that future research expand to include diverse family perspectives and methodologies to further benefit families navigating similar paths.